2021
DOI: 10.3389/fpsyg.2021.689251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wise Intervention on Perceived Discrimination Among College Students Returning Home From Wuhan During the COVID-19 Outbreak

Abstract: At the beginning of the coronavirus disease 2019 (COVID-19) outbreak, college students returning home from Wuhan, Hubei Province, experienced various degrees of discrimination. This study first investigates perceived discrimination among college students returning home from Wuhan. Then, an experimental method is used to investigate the effectiveness of an intervention designed to reduce the perceived discrimination among those who returned to towns outside of Hubei Province. A total of 63 college students part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… Stress, well-being, resilience [SQ] This research revealed that SOCI had significantly improved participants' resilience, spirituality, and positive growth over time but not post-traumatic stress or negative affect. Lu, T. et al, 2021 [EN] COVID-19 [2019] National RCT [3 months] 86 Adult [IL] N=63 [31 INT, 32 CON] 40 minutes Intervention: wise intervention. Control: unrelated reading and writing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Stress, well-being, resilience [SQ] This research revealed that SOCI had significantly improved participants' resilience, spirituality, and positive growth over time but not post-traumatic stress or negative affect. Lu, T. et al, 2021 [EN] COVID-19 [2019] National RCT [3 months] 86 Adult [IL] N=63 [31 INT, 32 CON] 40 minutes Intervention: wise intervention. Control: unrelated reading and writing.…”
Section: Resultsmentioning
confidence: 99%
“… 85 . 86 For example, in a trial about the effect of self-affirmation on anxiety, intervention-group participants performed self-affirmation writing exercises while control-group participants did unrelated writing exercises. 85 Similarly, in a study aimed at reducing perceived discrimination among people living in Wuhan during the COVID-19 epidemic, 86 intervention-group participants received a focused reading- and writing-based intervention while control-group participants did unrelated reading and writing.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al, 2023). In addition, undergraduates returning home from Wuhan report experiencing varying degrees of discrimination (Lu et al, 2021). Based on the above, the COVID-19 epidemic traumatizes Wuhan college students in multiple ways, and it is necessary to pay attention to the mental health of university students in Wuhan.…”
Section: Fear Of Covid-19 and Ptgmentioning
confidence: 99%
“…Studies have shown that local university students in Wuhan became irregular in their daily routines and had their academic activities disrupted during the quarantine period, which seriously affected their mental health (F. Liu et al, 2023). In addition, undergraduates returning home from Wuhan report experiencing varying degrees of discrimination (Lu et al, 2021). Based on the above, the COVID-19 epidemic traumatizes Wuhan college students in multiple ways, and it is necessary to pay attention to the mental health of university students in Wuhan.…”
mentioning
confidence: 99%
“…It was found by Clinton et al [ 172 ] that Positive Empathy Intervention (imagining positive contact with the stigmatized person and establishing a positive emotional connection) was superior to traditional contact methods in terms of stigma reduction[ 172 ]. Cognitive-behavioral Intervention and Wise Intervention have been shown to increase perceived social support and reduce self-stigma in individuals[ 173 , 174 ]. Furthermore, Visual Information Image Interventions[ 175 ] and Work Integration[ 176 ] assist individuals in gaining correct knowledge, changing perceptions, and enhancing social inclusion, thereby reducing stigma.…”
Section: The Intervention Of Psychiatrists’ Occupational Stigmamentioning
confidence: 99%